Muzara'ah Contract Agricultural Accounting Model - Susanti, Alifi Tria; Roziq, Ahmad; Prasetyo, Whedy (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
Profit sharing in the agricultural sector has been known for a long time, so it applies from generation to generation. Profit sharing is found in several areas, including Lumajang Regency, Tekung District which according to statistical data has a land area of ​​1,878.34 hectares and the majority of commodities are rice plants up to 4,342 hectares, but the number of profit sharing practices is not matched by regulations on accounting required by owners and land managers in being responsible for the distribution of business results. The purpose of this study is to analyze the agricultural production sharing system for the muzara'ah contract and produce an accounting model for the muzara'ah contract. The research method uses qualitative methods in general and phenomenology in particular. The results of this study prove that the practice of profit sharing practiced by the owners and managers of rice fields is a muzara'ah contract whose recording is done by simple recording. The accounting model produced in this study is an income statement, cash flow and profit sharing principle in accordance with the acknowledgment and muzara'ah contract.